Physiology-based patient simulator for blood pressure meter testing - Gregor Geršak (Measurement: Sensors, 2021)
Nowadays, the accuracy of automated oscillometric non-invasive blood pressure meters is evaluated in hospitals by means of clinical validations, in which the device’s measurements are compared to manually measured blood pressure, performed by trained medical staff using manual sphygmomanometers. Because of the clinical validations being costly, time demanding and logistically challenging, special devices for testing blood pressure meters were designed. This, so-called patient simulators are electromechanical devices capable of generating oscillometric signals. Using the very repeatable and stable simulators, blood pressure meters can be evaluated and their accuracy tested. Recently, a novel type of simulator, based on physiologically real-life oscillometric signals recorded on real patients, were introduced. First evaluations of the physiologically-based simulator are presented.